4(m+1)+7(-m+8)=75

Simple and best practice solution for 4(m+1)+7(-m+8)=75 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(m+1)+7(-m+8)=75 equation:


Simplifying
4(m + 1) + 7(-1m + 8) = 75

Reorder the terms:
4(1 + m) + 7(-1m + 8) = 75
(1 * 4 + m * 4) + 7(-1m + 8) = 75
(4 + 4m) + 7(-1m + 8) = 75

Reorder the terms:
4 + 4m + 7(8 + -1m) = 75
4 + 4m + (8 * 7 + -1m * 7) = 75
4 + 4m + (56 + -7m) = 75

Reorder the terms:
4 + 56 + 4m + -7m = 75

Combine like terms: 4 + 56 = 60
60 + 4m + -7m = 75

Combine like terms: 4m + -7m = -3m
60 + -3m = 75

Solving
60 + -3m = 75

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -60 + -3m = 75 + -60

Combine like terms: 60 + -60 = 0
0 + -3m = 75 + -60
-3m = 75 + -60

Combine like terms: 75 + -60 = 15
-3m = 15

Divide each side by '-3'.
m = -5

Simplifying
m = -5

See similar equations:

| 6+3x+3=15 | | y(y-7)-6=2 | | 2x+1+x+4= | | p=3t+2w | | 5n+3n=-12 | | -6(-2v+8)=5(-5v+5)+1 | | 2x-120=180 | | 8d^2+2d= | | -15.00+2.00x=-1 | | 3m-2(m-3)=3 | | 24=3x+6y | | 0.34x+5=9 | | 9x-6-3x=30 | | -5(k-8)+7(-5+k)=-3 | | 2x+10+3x=55 | | 2(u+8)=-6(3u-1)+8u | | 5(4v-5)=5v+4 | | 36=-9(-5+1) | | 8g-3(5+2g)=85-3g | | (3x-4)(7x+5)=0 | | 4y+10=180 | | x+32=3x+24 | | -3(8-7n-2)=18 | | 12f-15=12f-15 | | 14+8m=14-3m-5 | | 16m+4x=y | | 10x^2-36x+27=0 | | 3x-2x-4=17 | | 2(x-5)-(3x+6)=-13 | | In(3x)+In(2x)=3 | | 3(5x+4)+12=-8 | | V=pir |

Equations solver categories